Documenting Portrayals of Race/Ethnicity on Primetime Television over a 20‐Year Span and Their Association with National‐Level Racial/Ethnic Attitudes. (March 2015) - Tukachinsky, Riva; Mastro, Dana; Yarchi, Moran; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> The current study content analyzes the 345 most viewed U.S. television shows within 12 separate television seasons spanning the years 1987 to 2009. Using multilevel modeling, the results from this comprehensive content analysis then are used to predict national‐level racial/ethnic perceptions (between the years 1988 and 2008) with data from the American National Election Studies (ANES). Content analysis results reveal severe underrepresentation of Latinos, Asian Americans, and Native Americans, and a tendency to depict ethnic minorities stereotypically (e.g., overrepresentation of hyper‐sexualized Latino characters). Multilevel‐modeling analysis indicates that both the quantity and quality of ethnic media representations contributes to Whites' racial attitudes.